Three Essays on the Industrial Exploitation of Natural Resources in Africa - (:unkn) unknown (My University, 2023)
This dissertation aims at shedding light on the determinants and the consequences of the industrial exploitation of natural resources in the context of contemporary Africa in the three following chapters. The first chapter studies the relationship between overfishing and human migration in Africa. We find causal evidence that the competition which is created by industrial fishing vessels that overfish the African seas and deplete fish stocks, increases the flow of foreign population to OECD and European countries. Using the household-level data, we show that the macro-level findings are consistent in terms of mechanisms. We find evidence of an out-migration of young individuals from rural and coastal households in response to an increase of industrial fishing close to their homes. We put forward the mechanism of a negative income shock created by this competition of industrial fishing vessels. The second chapter analyses the effects of mining-induced water pollution on child mortality in Africa. We study water pollution indirectly as we compare the health outcomes of downstream villages downstream to those that are located upstream of a mining site before and after its opening. Compared to upstream individuals, our analysis finds that being downstream of an open mine increases the 24-month mortality rate by 25 %. The third chapter investigates how aid and credits from traditional and emerging donor countries influence their capacity to exploit natural resources in Africa over the 2000-2014 period. Results suggest that the official development flows from donor countries are positively correlated with their capacity to conclude large-scale land acquisitions.
Keywords: African Research